2006
DOI: 10.1007/s00134-006-0391-3
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive ventilation in chronic obstructive pulmonary disease patients: helmet versus facial mask

Abstract: Helmet and facial mask were equally tolerated and both were effective in ameliorating gas exchange and decreasing inspiratory effort. The helmet, however, was less efficient in decreasing inspiratory effort and worsened the patient-ventilator interaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
88
3
7

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(103 citation statements)
references
References 38 publications
5
88
3
7
Order By: Relevance
“…In accordance with previous studies, 12,13,[16][17][18] our results showed that the helmet does not perform as well as the face mask or ETT. Racca et al 19 demonstrated in 6 healthy volunteers that PSV delivered by a helmet was less effective in unloading the work of breathing compared with a face mask using the same level of support.…”
Section: Discussionsupporting
confidence: 92%
“…In accordance with previous studies, 12,13,[16][17][18] our results showed that the helmet does not perform as well as the face mask or ETT. Racca et al 19 demonstrated in 6 healthy volunteers that PSV delivered by a helmet was less effective in unloading the work of breathing compared with a face mask using the same level of support.…”
Section: Discussionsupporting
confidence: 92%
“…We observed non-supported inspiration only in high pressure support via face mask because triggering was difficult due to high PEEPi. 23,24,[26][27][28] By increasing cycling to 40%, non-supported inspiration could completely be avoided due to its effect on expiratory cycle latency. Due to impaired flow and pressure transmission, much longer inspiration time was necessary in the helmet to trigger a ventilator breath.…”
Section: Discussionmentioning
confidence: 99%
“…Without leakage we did not find any wasted efforts with the helmet and only very few occasions with the mask, whereas others observed increased non-supported inspirations. 18,19,23,26 This difference might be explained by a difference in PEEP, which affects pressure transmission and trigger sensitivity, inspiratory force, and the performance of the ventilator.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that NIV delivered via helmet is less efficient than via face mask in reducing inspiratory effort SEE THE ORIGINAL STUDY ON PAGE 15 and worsens patient-ventilator synchrony. [15][16][17][18][19] There has also been concern about CO 2 rebreathing with inspired P CO 2 being dictated by the amount of CO 2 produced by the subject and the amount of fresh gas flow flushing the large dead space in the helmet. 20,21 Higher flow in the helmet is required to overcome this, which may reduce patient comfort 22 The presence of rebreathing may create asynchrony by causing dyspnea and increased respiratory drive.…”
Section: Waiting To Exhale: Optimizing Noninvasive Synchrony In Copd?mentioning
confidence: 99%